Exploring local economic activities in reconstruction and development programme housing: case study of Mapleton Township - Nkadimeng, Patike Moffat (My University, 2009)
Economic activities are lacking in many townships around South Africa. The newly developed Reconstruction and Development Programme townships are also facing the problem of encouraging economic activities. These townships are always criticized for being overcrowded by the people who are unable to support economic activities because of lack of capacity to be employed. This study adopted assets pentagon method to find the assets which the people have in the township which they can use to support and encourage economic activities in the area. Assets Pentagon method includes social and political capital, human capital, physical capital, financial capital and natural capital. The availability of these assets in the township will be vital to encourage and support economic activities
Keywords: Social capital; Human capital; Financial capital; Physical capital; Natural capital